Analysis and Development of Academic Journals based on ASEAN Citation Index (ACI) Criteria - Sirirak, Kosin; Youngjeen, Sujinda; Monkeaw, Laddawan (Recent Science and Technology, 2020)
This study aimed to develop the quality of academic journals due to ASEAN Citation Index (ACI) criteria, reinforce the quality development of Walailak University academic journals, and operate the journals under the same standard. Walailak University academic journals were selected as secondary sources. The data were collected using ACI criteria, the pre-test and post-test, analyzing the potential for Walailak University’s journals, semi-structured interview with journal editors, and improving the journals due to ASEAN Citation Index (ACI) criteria. The results showed that Walailak University academic journals can be classified into two groups: (1) journals indexed in TCI tier 2 which are Walailak Abode of Culture Journal, and Journal of Learning Innovations Walailak University; and, (2) journals indexed in TCI tier 1 which are Walailak Journal of Social Sciences, and WMS Journal of Management. After sorting journals in accordance with 11 criteria of the ACI , it revealed that the score of WMS Journal of Management is more than 80% while the other three journals score less than 80% which are Walailak Abode of Culture Journal, Walailak Journal of Social Sciences, and Journal of Learning Innovations Walailak University, respectively. The results also revealed that the above four journals from Walailak University were aware of their strengths and weakness according to 11 criteria of the ACI database. The journals improved the timeliness of publication, required English version of reference, employed English editor, and created English-version website. These would help to develop journals’ quality, and provide systematic procedure to meet the same standard of ACI criteria. More suggestions were that the journals should accept more articles published in English to create opportunities for referencing articles in the international databases as well as improving the quality of the journal in accordance with the assessment criteria of universities and domestic organizations.